2018
DOI: 10.3892/etm.2018.5933
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect of astragalosides from Radix Astragali on adriamycin-induced podocyte injury

Abstract: Abstract. Nephrotic syndrome (NS) is the most common kidney disease in clinical practice and may lead to end-stage renal failure. Astragalosides (AST) have been clinically tested for the treatment of NS, but their mechanism of action has remained to be elucidated. The aim of the present study was to investigate the effect of AST on the structure and function of podocytes with adriamycin (ADR)-induced damage and to elucidate the underlying molecular mechanisms. The mouse podocyte clone 5 (MPC5) immortalized mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Podocytes are highly differentiated epithelial cells on the outer surface of glomerular capillaries [ 7 ], which play crucial roles in glomerular diseases. Podocyte injury has been considered as one critical factor in glomerular filtration barrier dysfunction, and continuous podocyte injury can lead to proteinuria, glomerulosclerosis, and renal impairment [ 8 – 10 ]. In addition, glomerulosclerosis, the main pathological process, can cause end-stage renal disease, and podocyte injury is crucial for the progression of glomerular disorders [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Podocytes are highly differentiated epithelial cells on the outer surface of glomerular capillaries [ 7 ], which play crucial roles in glomerular diseases. Podocyte injury has been considered as one critical factor in glomerular filtration barrier dysfunction, and continuous podocyte injury can lead to proteinuria, glomerulosclerosis, and renal impairment [ 8 – 10 ]. In addition, glomerulosclerosis, the main pathological process, can cause end-stage renal disease, and podocyte injury is crucial for the progression of glomerular disorders [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the cytotoxicity of CDK was specific to cancer cells, because CDK did not influence the viability of FHs 74 Int cells, suggesting that CBK may cause less adverse events in clinical settings. In addition, it is reported that Carapax Trionycis inhibits fibrogenesis of activated hepatic stellate cells [8], and Radix Astragali protects against podocyte injury in nephrotic syndrome [9]. The above data demonstrate that CBK is potentially superior to some chemotherapeutic anti-cancer agents, in terms of causing side effects.…”
Section: Discussionmentioning
confidence: 89%
“…MMP-9 plays a key role in podocyte injury, and podocyte migration and Adriamycin-induced cell injury may be related to the upregulation of MMP-9 expression. Sai et al (18) found that the expression levels of MMP-2 and MMP-9 were decreased in a doxorubicin-induced podocyte injury group, while the use of Astragali Radix in the intervention group inhibited this decrease and prevented podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, oral bioavailability (OB) and drug-likeness (DL) were used to screen out the chemical components with an OB ≥30% and a DL ≥0. 18.…”
Section: Collection and Screening Of Chemical Constituents Of Astragali Radixmentioning
confidence: 99%